2020
DOI: 10.4028/www.scientific.net/msf.1005.150
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Injection Molds Using Various 3D Printing Technologies

Abstract: This paper explores the possibility of using different 3d printing methods and materials in the production of polymer molds for injection molding applications. A mold producing a cube was designed using a commercial software. Following the standard 3d printing process, injection molds which could produce a cube were printed using different 3d printing materials and 3d printing technologies. The 3d printing technologies used were Stereolithography (SLA), Polyjet and Fused Filament Fabrication (FFF). A bench-top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…The weakness of the SLA molds was referred to as cracking, and chipping mechanisms occurred after 60 shots, which were mainly attributed to transverse tension and the thermal cycle, whereas layer delamination strongly limited (10 shots) the endurance of the FDM 3D-printed mold inserts. Again, the same authors [ 10 ] conducted injection molding tests with SLA, polyjet, and FDM mold inserts. A PEEK mold fabricated by FDM showed delamination, whereas mold inserts made by SLA and polyjet technologies showed good surface finishing and acceptable dimensional accuracy and stability, below 5%.…”
Section: Introductionmentioning
confidence: 99%
“…The weakness of the SLA molds was referred to as cracking, and chipping mechanisms occurred after 60 shots, which were mainly attributed to transverse tension and the thermal cycle, whereas layer delamination strongly limited (10 shots) the endurance of the FDM 3D-printed mold inserts. Again, the same authors [ 10 ] conducted injection molding tests with SLA, polyjet, and FDM mold inserts. A PEEK mold fabricated by FDM showed delamination, whereas mold inserts made by SLA and polyjet technologies showed good surface finishing and acceptable dimensional accuracy and stability, below 5%.…”
Section: Introductionmentioning
confidence: 99%
“…[212] Another study also observed that a combination of both the methods (3D-printing and injection molding), especially reduces the cost and enhances the production speed of printing. [40,213,214] Other findings also note that 3D-printing reduces the shipping and manufacturing costs and around 70% of prototyping costs involved in traditional manufacturing. [215] The digitallyenabled mechanisms of 3D printing techniques cut shorts a number of these processes, and thereby can be accessed at a cheap rate from any part of the world.…”
Section: D-printing Versus Conventional Methods In Covid Timesmentioning
confidence: 99%
“…[ 212 ] Another study also observed that a combination of both the methods (3D‐printing and injection molding), especially reduces the cost and enhances the production speed of printing. [ 40,213,214 ]…”
Section: D‐printed Medical and Safety Devicesmentioning
confidence: 99%
“…A most common way that these groups have contributed include activities in producing hundreds and even thousands of PPEs (face shields, masks, and venture valves). [48,95,96] (see Supplementary Material).…”
Section: D Printing Ppes At Organizations and Universitiesmentioning
confidence: 99%
“…Our group recently published a study regarding the possibility of combining AM (3D printing) and formative manufacturing (injection molding). [95,96] The cost and lead time for tooling/ mold fabrication will be significantly reduced when these two processes are combined. Therefore, the 3D-printed tool or die becomes a multiplier.…”
Section: Combination Of Am and Formative Manufacturingmentioning
confidence: 99%